2021
DOI: 10.1088/1755-1315/741/1/012018
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability of Citrus spp. in Cibinong germplasm garden using random amplified polymorphic DNA

Abstract: The preservation and protection of citrus plant germplasms can be done in-situ and ex-situ. Germplasm garden LIPI, Cibinong was built as a local fruit plant garden. The field management also carries out seed propagation and dissemination. This study aims to reveal the genetic diversity of citrus collections and used them as a database for plant breeding and protection activities. This research was conducted at the Agronomy Laboratory for Evaluation of Biotechnology Products-LIPI. Genetic analysis was performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…It indicated that the bioactive compounds of C. reticulata from different planting locations might differ from the same species (Abeysinghe et al 2007;Wang et al 2019;Wang et al 2020). The difference in secondary metabolites could be due to genetic variations, availability of nutrients, and environmental conditions where they are grown (Anggraheni 2021;Siagian et al 2021). In addition, the difference in the number of identified compounds may be influenced by the sensitivity of the LC-QTOF-MS/MS used.…”
Section: Identified Bioactive Compounds In Rgl Orange Extractmentioning
confidence: 99%
“…It indicated that the bioactive compounds of C. reticulata from different planting locations might differ from the same species (Abeysinghe et al 2007;Wang et al 2019;Wang et al 2020). The difference in secondary metabolites could be due to genetic variations, availability of nutrients, and environmental conditions where they are grown (Anggraheni 2021;Siagian et al 2021). In addition, the difference in the number of identified compounds may be influenced by the sensitivity of the LC-QTOF-MS/MS used.…”
Section: Identified Bioactive Compounds In Rgl Orange Extractmentioning
confidence: 99%
“…One of Indonesia's leading horticultural commodities is fruit, and Indonesia has local superior citrus species and varieties that are spread throughout the archipelago. Citrus is one of the world's major fruit crops [3], grown in many regions [4], which has high economic value [5]. Citrus fruits belong to the family Rutaceae and subfamily Aurantioideae and can be grown in tropical and sub-tropical climates [6].…”
Section: Introductionmentioning
confidence: 99%